PENGARUH BIAYA IKLAN PADA PENJUALAN DENGAN HUMAN CAPITAL SEBAGAI VARIABEL MODERATING - Imaningati, Sri (PRESTASI, 2013)
ABSTRACTÂ This study aimed to examine the effect of Advertisement Cost to Sale the Human Cwith Human Capital as moderating Variable for manufacturing companies in Indonesian Stock Exchange(IDX) from 2011 to 2012. Knowledge Based approach used in this study to explain the Human Cap ital function. Samples were taken in this study used purposive sampling. The analytical tool used is multiple regression analysis to look at the independent variables either jointly or individualy. The results showed that Advertisement Cost had positive effect on Sales and the relation can be strengthen by increase the Human Capital variable. Significant results are indicated by value greather than 0.05. Â Keywords : Advertising Cost, Sale, Human Capital.Â